2015
DOI: 10.4028/www.scientific.net/amm.789-790.141
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation to Improve Surface Integrity of Biomedical Devices by End-Milling AISI 316L Stainless Steel

Abstract: This paper presents the influence of machining parameters namely cutting speed and feed rate on the machinability enhancement of AISI 316L stainless steel, in terms of surface integrity using end-milling with coated tungsten carbide tool (TiAlN). Optical microscopy, Scanning Electron Microscopy (SEM) and surface roughness measurement were used to analyze the surface integrity in terms surface topography and hardness test. A multi view approach is adopted to study the effect of different cutting parameters on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…Kadi [27] obtained the optimal surface roughness (Ra = 1.664 µm) during dry cutting of 316L steel. Furthermore, Yasir et al [43] achieved a value of Ra = 0.537 µm when milling AISI 316L steel. It was found that a lower surface roughness value can be obtained at lower FR values (Figure 10).…”
Section: Surface Topography Analysismentioning
confidence: 99%
“…Kadi [27] obtained the optimal surface roughness (Ra = 1.664 µm) during dry cutting of 316L steel. Furthermore, Yasir et al [43] achieved a value of Ra = 0.537 µm when milling AISI 316L steel. It was found that a lower surface roughness value can be obtained at lower FR values (Figure 10).…”
Section: Surface Topography Analysismentioning
confidence: 99%
“…The thermo-mechanical model is built by ABAQUS, which owns a rich data of material and element type. The detailed modelling steps are as follows: (1) First, choose Johnson-cook model as the constitutive equations, due to its simple form and accurate descriptions of material behavior in high strain rate [47]; (2) Second, use physical criterion estimate chip separation conditions for drawing close to the reality [48]; (3) Third, set tangential and normal friction models in contact property, the former is based on penalty function with friction coefficient of 0.27, the latter takes hard contact to realize separation after contact [49].…”
Section: Comparisonmentioning
confidence: 99%
“…At the greatest cutting speed (V c = 140 m/min), the primary zone temperature was higher in comparison with lower cutting speed; this thermal state decreased the yield strength of material, decreasing the cutting force requirement to machine the material and resulting in a smoother surface. The formation of the BUE at a higher cutting speed was reduced along with the voids which improved the surface quality [43,44]. Figure 5 shows a 2D surface profile scan of the sample with lowest and highest Z (μm) value.…”
Section: Surface Roughnessmentioning
confidence: 99%